The Role of Social Deixis in Expressing Respect and Authority: A Study Of “Coco” - Assyifa, Noor Assyifa; Azhar, Nazwa Sahara; Nasution, Nazwa Amalia Putri; Silalahi, Kevindo (ENGLISH JOURNAL OF INDRAGIRI, 2026)
Social deixis is a key part of pragmatics that shows how language expresses respect, authority, and social ties in different cultures. Although deixis has been studied a lot, there is still not much research on how social deixis can show both authority and emotional bonds in stories with strong cultural and family themes, such as the animated film Coco. This study examines how social deixis is used in Coco (2017), focusing on how it reflects respect, authority, and emotional closeness between characters in Mexican culture. Using a qualitative descriptive method, the study reviews and analyzes all film dialogues with social deixis, sorting them into relational and absolute types based on Levinson’s theory. The findings show that relational social deixis, especially kinship terms and informal address, is most common, highlighting the importance of family ties and solidarity. Absolute deixis, though less common, points to respect and power differences. The study concludes that social deixis in Coco helps build cultural identity and share moral values, showing how film language connects cultural and emotional understanding. Future research could compare how social deixis appears in different cultures and media to deepen our understanding of language, culture, and communication.